Beneficial effects of liquid crystalline phases in solid-state dye-sensitized solar cells - Costa, Ruben Dario; Werner, Fabian; Wang, Xinjiao; Grönninger, Philipp; Feihl, Sebastian; Kohler, Florian; Wasserscheid, Peter; Hibler, Susanne; Beranek, Radim; Meyer, Karsten; Guldi, Dirk Michael (Advanced Energy Materials, 2013)
Two novel double-alkyl functionalized imidazolium ionic liquid crystals have successfully been utilized to demonstrate the benefits of the liquid crystalline phase on the ssDSSC performance. In particular, a good balance between dye regeneration and hole transport is only realized in the liquid crystalline phase. Devices that employ a single component ionic liquid based electrolyte show a remarkably stable efficiency during 1000 h under outdoor operation temperature conditions and 1 sun illumination. Two novel double-alkyl functionalized imidazolium ionic liquid crystals have successfully been utilized to demonstrate the benefits of the liquid crystalline phase on the ssDSSC performance. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Benzoporphyrins: Selective Co-sensitization in Dye-Sensitized Solar Cells - Lodermeyer, Fabian; Costa, Ruben Dario; Malig, Jenny; Jux, Norbert; Guldi, Dirk Michael (Chemistry - A European Journal, 2016)
A novel class of dyes, namely benzoporphyrins, was synthesized and implemented into dye-sensitized solar cells. They feature complementary absorptions compared to N719, which renders them promising candidates for co-sensitization in DSSCs. Notably, metallated benzoporphyrins reveal a TiO2-nanoparticle attachment that is size and aggregation dependent. Therefore, unproductive energy-transfer events between the selectively attached dyes can be prevented. In light of the latter, an efficiency improvement of 39 % has been achieved upon selective adsorption of benzoporphyrins and N719 onto different layers of TiO2 photoelectrode.
EAM Import::2019-03-13

Binary Indium-Zinc Oxide Photoanodes for Efficient Dye-Sensitized Solar Cells - Peukert, Wolfgang; Stanzel, Melanie; Kunzmann, Andreas; Guldi, Dirk Michael; Costa Riquelme, Rubén Dario (Advanced Energy Materials, 2016)
The benefits of incorporating binary metal-oxide electrodes en route toward efficient dye-sensitized solar cells (DSSCs) have recently emerged. The current work aims at realizing efficient indium-doped zinc oxide based DSSCs by means of enhancing charge transport processes and reducing recombination rates. Electrochemical impedance spectroscopic assays corroborate that low amounts of indium reduce charge transport resistances and increase electron recombination resistances. The latter are in concert with a remarkable enhancement of the charge collection efficiency from 33% to 83% for devices with ZnO and InZnO photoanodes, respectively. Going beyond 15 mol% of indium, an effective electron trapping increases the charge transport resistance and, in turn, dramatically reduces charge collection efficiency. Upon implementing InZnO into an electron cascade photoanode architecture featuring an InZnO bottom layer and a ZnO top layer, a device efficiency of 5.77% and a significantly high current density of 20.4 mA cm in binary ZnO DSSCs are achieved.
Keywords: binary oxides; charge collection efficiency; flame spray pyrolysis; indium-zinc oxide photoanodes; n-type DSSCs

Bioinspired Hybrid White Light-Emitting Diodes - Weber, Michael; Niklaus, Lukas; Pröschel, Marlene; Brana Coto, Pedro; Sonnewald, Uwe; Costa Riquelme, Rubén Dario (Advanced Materials, 2015)
The first bioinspired hybrid white-light-emitting diodes (bio-HLEDs) featuring protein cascade coatings are presented. For easy fabrication a new strategy to stabilize proteins in rubber-like material was developed. The synergy between the excellent features of fluorescent proteins and the easily processed rubber produces bio-HLEDs with less than 10% loss in luminous efficiency over 100 hours.

Carbon Nanohorn-based electrolyte for Dye-Sensitized Solar Cells - Lodermeyer, Fabian; Costa Riquelme, Rubén Dario; Casillas Pacheco, Ruben; Kohler, Florian; Wasserscheid, Peter; Prato, Maurizio; Guldi, Dirk Michael (Energy and Environmental Science, 2014)
For the first time, carbon nanohorns were implemented into solid-state electrolytes for highly efficient solid-state and quasi-solid-state DSSCs. They feature an effective catalytic behavior towards the reduction of I3- and enhance the I3- diffusivity into the electrolyte. In a final device, solar cells with 7.84% efficiency at room temperature were achieved. As a matter of fact, this is the highest reported efficiency for nanocarbon-based electrolytes up to date.

Carbon Nanohorns as Integrative Materials for Efficient Dye-Sensitized Solar Cells - Costa Riquelme, Rubén Dario; Feihl, Sebastian; Kahnt, Axel; Gambhir, Sanjeev; Officer, David L.; Wallace, Gordon G.; Lucio, Mara Isabel; Herrero, Mara Antonia; Vzquez, Ester; Syrgiannis, Zois; Prato, Maurizio; Guldi, Dirk Michael (Advanced Materials, 2013)
Different nanocarbons, that is, single-wall carbon nanotubes, graphene, single-wall carbon nanohorns (SWCNHs), and their respective oxidized analogs have been used to fabricate novel doped TiO2 electrodes for DSSCs. Our results indicate that all of the nanocarbons significantly enhance the device characteristics when compared to standard TiO2 electrodes. Overall, our most outstanding finding is that SWCNH derivatives are also a plausible material for developing highly-efficient DSSCs.

Carbon nanomaterials as integrative components in dye-sensitized solar cells - Costa, Ruben Dario; Guldi, Dirk Michael (Nanocarbon-Inorganic Hybrids: Next Generation Composites for Sustainable Energy Applications, 2014)
One of the major challenges that humanity faces is the development of renewable energy resources to secure our current lifestyle. In fact, linking problems such as pollution and globalwarming to the use of fossil fuels as an energy source is eye opening [1-3]. In this context, different renewable energy sources such as windmill-powered plants, hydropower, biomass production, geothermal power, and solar energy are currently under scrutiny. Among the aforementioned, solar energy bears one of the greatest potentials for securing the current energy supply. This notion is based on the amount of energy that reaches the earth’s surface at zero costs and at continuous supply. Notably, one hour of solar irradiation covers more than theworld’s current energy demand for a complete year. As such, photovoltaic devices/solar cells are considered as a superior means of energy harvesting [2, 4, 5].
CRIS-Team Scopus Importer:2023-03-07

Choosing the right nanoparticle size-designing novel ZnO electrode architectures for efficient dye-sensitized solar cells - Pfau, Markus; Kunzmann, Andreas; Segets, Doris; Peukert, Wolfgang; Wallace, Gordon G.; Officer, David L.; Clark, Timothy; Costa, Ruben Dario; Guldi, Dirk Michael (Journal of Materials Chemistry A, 2017)
A novel concept for constructing optimized ZnO-based photoanodes as integrative components of dye-sensitized solar cells (DSSCs) is realized by deploying differently sized nanoparticles, ranging from 2 to 10 nm, together with commercially available 20 nm nanoparticles. The 2 nm nanoparticles were used to construct an efficient buffer layer for transparent electrodes based on 10 nm nanoparticles, resulting in a relative increase of device efficiency from 1.8 to 3.0% for devices without and with a buffer layer, respectively. A mixture of 10 and 20 nm nanoparticles was optimized to maximize the diffuse reflection and to minimize the charge transport resistance in a light-scattering layer. This optimization resulted in a homogenous layer of more than 15 mm that provided a device efficiency of 3.3%. The buffer layer, transparent electrode, and light-scattering electrode, were then combined to give an overall efficiency of around 5%. Thus, this work demonstrates that varying the electrode architecture with nanoparticles of different diameters is a powerful strategy for improving the overall efficiency of ZnO-based DSSCs.

Combining Electron-Accepting Phthalocyanines and Nanorod-like CuO Electrodes for p-Type Dye-Sensitized Solar Cells - Langmar, Oliver; Ganivet, Carolina R.; Lennert, Annkatrin; Costa, Ruben Dario; De La Torre, Gema; Torres, Tomas; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2015)
A route is reported for the synthesis of two electron-accepting phthalocyanines featuring linkers with different lengths as sensitizers for p-type dye-sensitized solar cells (DSSCs). Importantly, our devices based on novel nanorod-like CuO photocathodes showed high efficiencies of up to 0.191 %: the highest value reported to date for CuO-based DSSCs.
EAM Import::2019-03-13

Controlling Interfacial Charge Transfer and Fill Factors in CuO-based Tandem Dye-Sensitized Solar Cells - Langmar, Oliver; Fazio, Ettore; Schol, Peter; De La Torre, Gema; Costa, Ruben Dario; Torres, Tomas; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2019)
We designed and synthesized a series of novel electron-accepting zinc(II)phthalocyanines (ZnPc) and probed them in p-type dye sensitized solar cells (p-DSSCs) by using CuO as photocathodes. By realizing the right balance between interfacial charge separation and charge recombination, optimized fill factors (FFs) of 0.43 were obtained. With a control over fill factors in p-DSSCs in hand we turned our attemtion to i-DSSCs, in which we combined for the first time CuO-based p-DSSCs with TiO2 -based n-DSSCs using ZnPc and N719. In the resulting t-DSSCs, the V-OC of 0.86 V is the sum of those found in p- and n-DSSCs, while the FF remains around 0.63. It is only the smaller J(SC)s in t-DSSCs that limits the efficiency to 0.69%.
CRIS-Team WoS Importer:2019-04-12

Controlling the Chromaticity of Small-Molecule Light-Emitting Electrochemical Cells Based on TIPS-Pentacene - Weber, Michael; Adam, Matthias; Tykwinski, Rik; Costa, Ruben Dario (Advanced Functional Materials, 2015)
This work demonstrates a novel proof-of-concept to implement pentacene derivatives as emitters for the third generation of light-emitting electrochemical cells based on small-molecules (SM-LECs). Here, a straightforward procedure is shown to control the chromaticity of pentacene-based lighting devices by means of a photoinduced cycloaddition process of the 6,13-bis(triisopropylsilylethynyl) (TIPS)-pentacene that leads to the formation of anthracene-core dimeric species featuring a high-energy emission. Without using the procedure, SM-LECs featuring deep-red emission with Commission Internationale d'Eclairage (CIE) coordinates of x = 0.69/y = 0.31 and irradiance of 0.4 extgreekmW cm-2 are achieved. After a careful optimization of the cycloaddition process, warm white devices with CIE coordinates of x = 0.36/y = 0.38 and luminances of 10 cd m-2 are realized. Here, the mechanism of the device is explained as a host–guest system, in which the dimeric species acts as the high-energy band gap host and the low-energy bandgap TIPS-pentacene is the guest. To the best of the knowledge, this work shows the first warm white SM-LECs. Since this work is based on the archetypal TIPS-pentacene and the photoinduced cycloaddition process is well-knownfor any pentacenes, this proof-of-concept could open a new way to use these compounds for developing white lighting sources.
EAM Import::2019-03-13

Designing Squaraines to Control Charge Injection and Recombination Processes in NiO-based Dye-Sensitized Solar Cells - Langmar, Oliver; Saccone, Davide; Amat, Anna; Fantacci, Simona; Viscardi, Guido; Barolo, Claudia; Costa, Ruben Dario; Guldi, Dirk Michael (ChemSusChem, 2017)
Herein, the synthesis of a new family of squaraines (SQs) and their application in p-type dye-sensitized solar cells (DSSCs) is presented. In particular, two sets of SQs were designed featuring either two or four anchoring carboxylic groups combined with either oxygen or dicyanovinyl central groups. The SQs were characterized by using a joint theoretical, photophysical, and electrochemical approach. Importantly, the presence of different central groups forces a frozen cis (dicyanovinyl group) or a trans (oxygen group) SQ conformation. Based on the latter, the current work enables a direct comparison between cis and trans isomers as well as the impact of a different number of anchors. Considering their electron-accepting and light-harvesting character, they were tested in NiO-based DSSCs. Photocurrent-voltage, incident photon-to-current conversion efficiency (IPCE), and electrochemical impedance spectroscopy measurements were performed. By virtue of their different symmetry, stereochemistry, and number of carboxylic groups, altered adsorption behavior onto NiO electrodes as well as diverse charge injection and charge recombination dynamics were noted under operation conditions. SQs with four linkers in a frozen cis isomerism show the best charge collection properties among the investigated SQs, providing a valuable guideline for the molecular design of future SQs for p-type DSSCs. In addition, we assembled tandem DSSCs featuring SQ/NiO photocathodes and N719/TiO2 photoanodes. The IPCE of the resulting tandem DSSCs implies light harvesting throughout most of the visible part of the solar spectrum owing to the complementary absorption features of SQ and N719.
EAM Import::2019-03-13

Easy and versatile coating approach for long-living white hybrid light-emitting diodes - Niklaus, Lukas; Dakhil, Haider; Kostrzewa, Monika Maria; Brana Coto, Pedro; Sonnewald, Uwe; Wierschem, Andreas; Costa Riquelme, Rubén Dario (Materials Horizons, 2016)
Herein, we provide a new easy-to-do protocol for preparing luminescent rubber-like materials based on a wide palette of compounds, such as small-molecules, quantum dots, polymers, and coordination complexes. The combination of this new protocol with that for preparing similar rubbers based on fluorescent proteins states the universal character of our approach. This is further assessed by using comprehensive spectroscopic and rheological investigations. Furthermore, the novel luminescent rubbers are applied as downconverting packing systems to develop white hybrid light-emitting diodes (WHLEDs), which are heralded as a solid alternative to achieve energy-saving, solid-state, and white-emitting sources in the coming future. As such, the current work also provides a clear prospect of this emerging lighting technology by means of a direct comparison among WHLEDs fabricated with all the above-mentioned down-converting systems. Here, the use of rubbers based on coordination complexes outperforms the others in terms of both luminous efficiency and colour quality with an unprecedented stability superior to 1000 h under continuous operation conditions. This represents an order of magnitude enhancement compared to the state-of-the-art WHLEDs, while keeping luminous efficiencies of around 100 lm W-1.

Electroluminescence: From White to Red: Electric-Field Dependent Chromaticity of Light-Emitting Electrochemical Cells based on Archetypal Porphyrins (Adv. Funct. Mater. 37/2016) - Weber, Michael; Wittmann, Judith; Burger, Alexandra; Malcioglu, Osman; Segarra-Martí, Javier; Hirsch, Andreas; Coto, Pedro B.; Bockstedte, Michel Georg; Costa, Ruben Dario (Advanced Functional Materials, 2016)
CRIS-Team Scopus Importer:2023-03-07
Keywords: collinear and vicinal regioisomers; electric-field dependent chromaticity; light-emitting electrochemical cells; tetraphenyl porphyrin; thin-film white-emitting sources

Electron accepting porphycenes on graphene - Costa, Ruben Dario; Malig, Jenny; Brenner, Wolfgang; Jux, Norbert; Guldi, Dirk Michael (Advanced Materials, 2013)
The versatility of nanographene (NG) as an electron donor is demonstrated when integrated together with an electron accepting porphycene into a novel electron NG hybrid. This feature is further exploited in dye-sensitized solar cells (DSSCs), in which photoanodes (ZnO) reveal a cascade of electron flow as modus operandi. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Facile and quick preparation of carbon nanohorn-based counter electrodes for efficient dye-sensitized solar cells - Lodermeyer, Fabian; Prato, Maurizio; Costa, Ruben Dario; Guldi, Dirk Michael (Nanoscale, 2016)
For the first time, Pt-free counter electrodes based on carbon nanohorns for highly efficient dye-sensitized solar cells were assembled by a facile and fast drop cast technique. These novel electrodes feature an effective catalytic behavior towards the reduction of I3- and, as such, afford even higher short-circuit current densities compared to Pt-based references. In a final device, solar cells with 7.7% efficiency were achieved.
EAM Import::2019-03-14

Hybrid Dye-Titania Nanoparticles for Superior Low-Temperature Dye-Sensitized Solar Cells - Kunzmann, Andreas; Valero, Silvia; Sepulveda, Angel E.; Rico-Santacruz, Marisa; Lalinde, Elena; Berenguer, Jesus R.; Garcia-Martinez, Javier; Guldi, Dirk Michael; Serrano, Elena; Costa Riquelme, Rubén Dario (Advanced Energy Materials, 2018)
In this work, a new strategy to design low-temperature (≤200 °C) sintered dye-sensitized solar cells (lt-DSSC) is reported to enhance charge collection efficiencies (ηcoll), photoconversion efficiencies (η), and stabilities under continuous operation conditions. Realization of lt-DSSC is enabled by the integration of hybrid nanoparticles based on TiO2-Ru(II) complex (TiO2_Ru_IS)—obtained by in situ bottom-up construction of Ru(II) N3 dye-sensitized titania—into the photoelectrode. Incentives for the use of TiO2_Ru_IS are i) dye stability due to its integration into the TiO2 anatase network and ii) enhanced charge collection yield due to its significant resistance toward electron recombination with electrolytes. It is demonstrated that devices with single-layer photoelectrodes featuring blends of P25 and TiO2_Ru_IS give rise to a 60% ηcoll relative to a 46% ηcoll for devices with P25-based photoelectrodes. Responsible for this trend is a better charge transport and a reduced electron recombination. When using a multilayered photoelectrode architecture with a top layer based only on TiO2_Ru_IS, devices with an even higher ηcoll (74%) featuring a η of around 8.75% and stabilities of 600 h are achieved. This represents the highest values reported for lt-DSSC to date.
CRIS-Team Scopus Importer:2022-04-14
Keywords: charge collection efficiency; dye-sensitized solar cells; hybrid dye-titania nanoparticles; low temperature sintering; multilayered electrodes

Hydrogen bonding mediated orthogonal and reversible self-assembly of porphyrin sensitizers onto TiO2 nanoparticles - Zeininger, Lukas; Lodermeyer, Fabian; Costa Riquelme, Rubén Dario; Guldi, Dirk Michael; Hirsch, Andreas (Chemical Communications, 2016)
We report on the orthogonal, highly directional and reversible self-assembly of porphyrins onto TiO2 nanoparticles by means of hydrogen bonding interactions. Unifying the stable covalent surface attachment of tailored, synthesized Hamilton receptors with the advantages of a non-covalent supramolecular immobilization of porphyrin cyanurates resulted in a redox- and photo-active nanohybrid. The latter was successfully implemented into a new type of supramolecular dye-sensitized solar cells.

Implementation of Single-Walled Carbon Nanohorns into Solar Cell Schemes - Lodermeyer, Fabian; Costa, Ruben Dario; Guldi, Dirk Michael (Advanced Energy Materials, 2017)
Recent advances in dye-sensitized solar cells (DSSC), including the use of nanocarbons, resulted in breakthroughs relevant to both the academic and industrial sectors. Their relevance encompasses, on one hand, the development and integration of novel nanocarbon/dye hybrids for superior light-harvesting and improved charge injection properties and, on the other hand, the integration of nanocarbons into each part of DSSCs for enhancing the charge collection efficiency as well as the dye and electrolyte regeneration processes. In the context of the earlier, control over the electron injection and recombination rates is realized on the molecular level. In the context of the latter, i) the charge transport and charge collection efficiencies in the photoelectrode are increased, ii) the charge recombination processes are reduced, when used as a nanocarbon-based buffer layer, iii) the ion diffusion and catalytic effects into (quasi) solid-state electrolytes are improved, and iv) devices using Pt-free counter electrodes with similar device efficiencies are realized. Leading examples of nanocarbons are graphene, carbon black, multi-walled carbon nanotubes, and single-walled carbon nanotubes. In this review, the focus is on a novel carbon allotrope, namely single-walled carbon nanohorns (SWCNH), which is discussed in depth and in comparison with other nanocarbons.
EAM Import::2019-03-13

Improving charge injection and charge transport in CuO-based p-type DSSCs-a quick and simple precipitation method for small CuO nanoparticles - Langmar, Oliver; Ganivet, Carolina R.; Schol, Peter; Scharl, Tobias; De La Torre, Gema; Torres, Tomas; Costa Riquelme, Rubén Dario; Guldi, Dirk Michael (Journal of Materials Chemistry C, 2018)
Herein, we introduce a co-precipitation synthesis of CuO, which produces small and uniform nanoparticles (∼12 nm) with a specific surface area of 97.3 m2 g-1. The resulting CuO nanoparticles are superior to the commercial ones, which have previously been used to prepare p-type DSSCs. In turn, we compared p-type DSSCs consisting of CuO-based photocathodes based on newly synthesized and commercial nanoparticles. Devices based on new CuO nanoparticles enable higher dye loadings, and, in turn, superior short-circuit current densities and efficiencies. To corroborate our findings, electrochemical impedance spectroscopy and intensity modulated photocurrent spectroscopy assays were conducted, revealing a better charge injection and faster charge transport for those photocathodes featuring the new CuO nanoparticles.
CRIS-Team Scopus Importer:2022-04-14

Iodine-Pseudohalogen Ionic Liquid-Based Electrolytes for Quasi-Solid-State Dye-Sensitized Solar Cells - Lennert, Annkatrin; Sternberg, Michelle; Meyer, Karsten; Costa, Ruben Dario; Guldi, Dirk Michael (ACS Applied Materials and Interfaces, 2017)
In the current work, novel symmetrically alkyl-substituted imidazolium-based ionic liquids have been synthesized featuring either iodide (I-) or selenocyanate (SeCN-) as counteranions. Physicochemical assays based on spectroscopy and electrochemistry techniques have been performed to identify the best ionic liquid for application as electrolytes in quasi-solid-state dye-sensitized solar cells (qssDSSC). The latter were mixed with additives such as 4-tert-butylpyridine (4tbpy) and guanidinium thiocyanate (GuSCN) to optimize electrode surface coverage, ionic diffusion, and dye regeneration. In addition, we demonstrate that electrolytes containing a mixture of I2 and (SeCN)2 enhance the open-circuit voltage of the final quasi-solid-state device by up to 70 mV. As such, iodine-pseudohalogen electrolytes reveal in qssDSSCs a good balance between dye regeneration and hole transport and, in turn, enhance the overall solar energy conversion efficiency by 70% with respect to reference qssDSSCs with iodine-based electrolytes. Finally, devices with the iodine-pseudohalogen electrolyte show a 1000 h stable efficiency of 7-8% under outdoor temperature operation conditions and 1 sun illumination.
EAM Import::2019-03-13

Layer-by-Layer Assemblies of Catechol-Functionalized TiO2 Nanoparticles and Porphyrins through Electrostatic Interactions - Burger, Alexandra; Costa, Ruben Dario; Lobaz, Volodymyr; Peukert, Wolfgang; Hirsch, Andreas; Guldi, Dirk Michael (Chemistry - A European Journal, 2015)
In the current work, we present the successful functionalization and stabilization of P-25 TiO2 nanoparticles by means of N1,N7-bis(3-(4-tert-butyl-pyridium-methyl)phenyl)-4-(3-(3-(4-tert-butyl-pyridinium-methyl)phenylamino)-3-oxopropyl)-4-(3,4-dihydroxybenzamido)heptanediamide tribromide (1). The design of the latter is aimed at nanoparticle functionalization and stabilization with organic building blocks. On one hand, 1 features a catechol anchor to enable its covalent grafting onto the TiO2 surface, and on the other hand, positively charged pyridine groups at its periphery to prevent TiO2 agglomeration through electrostatic repulsion. The success of functionalization and stabilization was corroborated by thermogravimetric analysis, dynamic light-scattering, and zeta potential measurements. As a complement to this, the formation of layer-by-layer assemblies, which are governed by electrostatic interactions, by alternate deposition of functionalized TiO2 nanoparticles and two negatively charged porphyrin derivatives, that is, 5,10,15,20-(phenoxyacetic acid)-porphyrin (2) and 5,10,15,20-(4-(2-ethoxycarbonyl)-4-(2-phenoxyacetamido)heptanedioic acid)-porphyrin (3), is documented. To this end, the layer-by-layer deposition is monitored by UV/Vis spectroscopy, scanning electron microscopy, ellipsometry, and profilometry techniques. The resulting assemblies are utilized for the construction and testing of novel solar cells. From stable and repeatable photocurrents generated during several ön-offc̈ycles of illumination, we derive monochromatic incident photo-to-current conversion efficiencies of around 3 \

Light-Emitting Electrochemical Cells Based on Hybrid Lead Halide Perovskite Nanoparticles - Aygueler, Meltem F.; Weber, Michael; Puscher, Bianka; Medina, Dana D.; Docampo, Pablo; Costa, Ruben Dario (Journal of Physical Chemistry C, 2015)
Methylammonium lead bromide (MAPbBr3) perovskite nanoparticles (NPs) have been recently proposed as a new material for light-emitting diodes, as well as a new paradigm to elucidate the operational mechanism in perovskite solar cells. Here, we have expanded the synthesis concept to fabricate NPs based on formamidinium lead bromide (FAPbBr3). Importantly, we have demonstrated that the photophysical features of this novel material can be easily tuned by exchanging the organic cation, achieving lower radiative bimolecular recombination rate for FAPbBr3 NPs. Additionally, we report for the first time light-emitting electrochemical cells (LECs) based on perovskite NPs by an easily up-scalable spray-coating technique. Stable luminance of 1–2 cd/m2 at low driving currents was achieved for both types of materials. Overall, this work opens a new avenue of research into the field of organic–inorganic metal halide nanoparticles bearing different alkyl ammonium groups and their application in the developing field of thin-film lighting devices.
EAM Import::2019-03-12

Modifying the Semiconductor/Electrolyte Interface in CuO p-Type Dye-Sensitized Solar Cells: Optimization of Iodide/Triiodide-Based Electrolytes - Langmar, Oliver; Ganivet, Carolina R.; Scharl, Tobias; De La Torre, Gema; Torres, Tomas; Costa, Ruben Dario; Guldi, Dirk Michael (ACS Applied Energy Materials, 2018)
Studies related to novel electrolyte concepts for p-type dye-sensitized solar cells (p-DSSCs) set focus on developing alternatives to the iodide/triiodide (I-/I-3(-)) redox couples, while attempts to improve the performance of the latter are scarce. In this study, we report on the first complete optimization of an I-/I-3(-)-based electrolyte for p-DSSCs employing CuO-based photocathodes. Optimization of the electrolyte solvent, the effect of ionic liquids, and the concentration-dependent properties of various electrolyte additives were at the focal point. Electrochemical impedance spectroscopy and intensity-modulated photovoltage and photocurrent spectroscopies complemented basic electrochemical and device characterization, leading to a sound understanding of charge injection, charge recombination, and charge transport. To this end, optimization of the aforementioned parameters enabled 2-fold device efficiencies of 0.156% compared to 0.078% for nonoptimized devices.
CRIS-Team WoS Importer:2019-03-01

Nanocarbon hybrids: The paradigm of nanoscale self-ordering/self-assembling by means of charge transfer/doping interactions - Guldi, Dirk Michael; Costa Riquelme, Rubén Dario (Journal of Physical Chemistry Letters, 2013)
The scope of this Perspective is to highlight the potential of nanoscale self-ordering/self-assembling nanocarbons - fullerenes, single-wall carbon nanotubes, and graphene - en route toward novel charge transfer hybrids that unify several functions such as light harvesting, charge separation, and, eventually, catalysis. All of the given examples are fully characterized by a broad range of spectroscopic as well as microscopic techniques and, as such, document the success in tuning the electronic structure of functional nanocarbons by means of charge transfer/doping interactions. © 2013 American Chemical Society.

N-Heterotriangulene chromophores with 4-pyridyl anchors for dye-sensitized solar cells - Meinhardt, Ute; Lodermeyer, Fabian; Schaub, Tobias; Kunzmann, Andreas; Dral, Pavlo O.; Sale, Anna Chiara; Hampel, Frank; Guldi, Dirk Michael; Costa, Ruben Dario; Kivala, Milan (RSC Advances, 2016)
A series of dimethylmethylene-bridged N-heterotriangulenes decorated with one, two, and three electron-withdrawing 4-pyridyls were synthesized. Their photophysical and electrochemical characteristics were examined and their successful application in n-type TiO2- and ZnO-based dye-sensitized solar cells demonstrated the ability of the 4-pyridyl moiety to act as an anchor.
EAM Import::2019-03-12

Nickel oxide nanostructured electrodes towards perylenediimide-based dye-sensitized solar cells - Feihl, Sebastian; Costa Riquelme, Rubén Dario; Pflock, Stephan; Schmidt, Cordula; Schönamsgruber, Jörg; Backes, Susanne; Hirsch, Andreas; Guldi, Dirk Michael (RSC Advances, 2012)
In this work, we have realized nickel oxide (NiO) electrodes that serve as photocathodes in p-type dye-sensitized solar cells (p-DSSCs) sensitized by dendronized perylenediimides (PDIs). To this end, two different approaches in terms of preparing NiO nanoparticle pastes were pursued to fabricate mesoporous electrodes on conductive fluorine doped tin oxide (FTO) glass substrates. Firstly, commercially available NiO nanoparticles were dispersed in a mixture of ethanol and terpineol. Here, in order to obtain a mesoporous network two types of ethylcelluloses (EC), that is, EC 5-15 and 30-50 mPa s, were added in 1:1 weight ratios. Following the evaporation of ethanol, the resulting pastes were spread on FTOs by doctor blading and calcinated at different temperatures. Importantly, the calcination temperature evolved as a crucial aspect in developing efficient electrodes. Nevertheless, the visual appearance of these NiO electrodes prompts a fairly heterogeneous coverage. To circumvent the aforementioned problem, a second approach en route to homogenous electrodes was investigated. In that particular case, commercial NiO nanoparticles were mixed with a mixture of EC 5-15 and 30-50 mPa s at a 1:1 weight ratio, with triacetin as a plasticizer in ethanol. In doing so, pastes containing 7 wt% EC, 3 wt% triacetin, and 3 to 20 wt% NiO nanoparticles were prepared. Most importantly, scanning electron microscopy (SEM) images corroborated the fact that the resulting electrodes revealed a dense coverage on FTOs. In addition, further characterizations ranging from UV/Vis transmission spectroscopy and conductivity measurements to Barrett-Joyner-Halenda (BJH) pore size and volume analysis were carried out. In the final step, the applicability of the new NiO photoelectrodes for p-DSSCs was successfully demonstrated by utilizing two types of PDIs, namely a symmetric 1 and a non-symmetric dendronized 2. Key aspects such as time dependence of dye uptake, hole lifetime and resistance features of the electrodes under operation conditions were investigated. © 2012 The Royal Society of Chemistry.

Novel nanographene/porphyrin hybrids-preparation, characterization, and application in solar energy conversion schemes - Kießling, Daniel; Costa, Ruben Dario; Katsukis, Georgios; Malig, Jenny; Lodermeyer, Fabian; Feihl, Sebastian; Roth, Alexandra Marina; Wibmer, Leonie; Kehrer, Matthias; Volland, Michel; Wagner, Pawel; Wallace, Gordon G.; et al. (Chemical Science, 2013)
Four novel nanographene/porphyrin hybrids were prepared, characterized, and probed in solar energy conversion schemes. Exfoliation of graphite by means of immobilizing four different porphyrins onto the basal plane of graphene is accompanied by distinct electronic interactions in both the ground and the excited states. In the ground state, a strong loss in oscillator strength goes hand-in-hand with a notable broadening of the porphyrin transitions and, as such, attests to the shift of electron density from the electron donating porphyrins to nanographene. In the excited state, a nearly quantitative quenching of the porphyrin fluorescence is indicative of full charge transfer. The latter is corroborated by femtosecond transient absorption measurements, which reveal the generation of the one-electron oxidized radical cation of the porphyrins with absorption maxima at 490 and 625 nm in the visible region and conduction band electrons in nanographene with features at 890 and 1025 nm in the near infrared region. We have demonstrated the applicability of the new nanographene/porphyrin hybrids in, for example, solar cells. In this regard, the presence of flakes is crucial in terms of influencing the injection processes, preventing aggregation, and reducing recombination losses, which are commonly encountered in porphyrin-based DSSCs. © 2013 The Royal Society of Chemistry.

Optimizing CuO p-type dye-sensitized solar cells by using a comprehensive electrochemical impedance spectroscopic study - Langmar, Oliver; Ganivet, Carolina R.; De La Torre, Gema; Torres, Tomas; Costa, Ruben Dario; Guldi, Dirk Michael (Nanoscale, 2016)
We introduce a novel and comprehensive approach for the evaluation and interpretation of electrochemical impedance spectroscopy (EIS) measurements in p-type DSSCs. In detail, we correlate both the device performance and EIS figures-of-merit of a series of devices in which, the calcination temperature, film thickness, and electrolyte concentration have been systematically modified. This new approach enables the separation of the different processes across the dye/semiconductor/electrolyte interface, namely the unfavorable charge recombination and the favorable electron injection/regeneration processes. In addition, studies on non-sensitized CuO and NiO electrodes provide insights into their affinity towards a reaction with the electrolyte - CuO is far less reactive towards the polyiodide species. Overall, this work underlines the superior features of CuO with respect to NiO for p-DSSCs and demonstrates a comprehensive optimization of the CuO-based DSSCs with respect to the device architecture by the aid of EIS analysis.
EAM Import::2019-03-08

Porphyrins as Multifunctional Interconnects in Networks of ZnO Nanoparticles and their Application in Dye-Sensitized Solar Cells - Düring, Jasmin; Kunzmann, Andreas; Killian, Manuela; Costa, Ruben Dario; Guldi, Dirk Michael; Gröhn, Franziska (Chemphotochem, 2018)
ZnO nanoparticles of 2.6 to 4.0 nm in size were interconnected by meso-tetra(4-carboxyphenyl)porphyrin (TCPP) for the realization of novel ZnO–TCPP networks, reaching lateral dimensions ranging from 50 to 800 nm. The resulting ZnO–TCPP networks were probed by dynamic light-scattering experiments, transmission electron microscopy, and spectroscopy, and were also tested as photoactive top layers in TiO2 and ZnO dye-sensitized solar cells (DSSCs). Control over these ZnO–TCPP networks on top of the semiconductor electrodes enables efficiency increases of 10 % and 46 % for TiO2- and ZnO-based photoelectrodes, respectively. In other words, effects, such as reducing the electron recombination and increasing the electron lifetime, document the benefits of using tailored functional hybrid systems in DSSCs.
CRIS-Team Scopus Importer:2022-04-14
Keywords: dye-sensitized solar cells; electron transfer; hybrid assemblies; porphyrins; semiconductor nanoparticles

Probing charge transfer in benzodifuran-C60 dumbbell-type electron donor-acceptor conjugates: Ground- and excited-state assays - Li, Hui; Schubert, Christina; Dral, Pavlo; Costa, Ruben Dario; La Rosa, Andrea; Thüring, Jürg; Liu, Shi-Xia; Yi, Chenyi; Filippone, Salvatore; Martín, Nazario; Decurtins, Silvio; Clark, Timothy; et al. (ChemPhysChem, 2013)
Rigid electron donor-acceptor conjugates (1-3) that combine π-extended benzodifurans as electron donors and C molecules as electron acceptors with different linkers have been synthesized and investigated with respect to intramolecular charge-transfer events. Electrochemistry, fluorescence, and transient absorption measurements revealed tunable and structure-dependent charge-transfer processes in the ground and excited states. Our experimental findings are underpinned by density-functional theory calculations. Dumbbell arrays: A benzodifuran (BDF) donor is for the first time fused to two C molecules by different linkers to form triads 1-3 (see figure). Their redox behavior, absorption, fluorescence emission, and photoinduced intramolecular charge-transfer events have been investigated experimentally and theoretically. The lifetime of the resulting charge-separated state varies distinctly with the polarity of the solvents and the distance between the BDF and C units. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Quaternized Pyridyloxy Phthalocyanines Render Aqueous Electron-Donor Carbon Nanotubes as Unprecedented Supramolecular Materials for Energy Conversion - Anaya-Plaza, Eduardo; Moreno-Oliva, Maria; Kunzmann, Andreas; Romero-Nieto, Carlos; Costa, Ruben Dario; De La Escosura, Andres; Guldi, Dirk Michael; Torres, Tomas (Advanced Functional Materials, 2015)
Exploring new properties in known materials, sometimes even achieving behaviors opposite to those traditionally encountered, is a fundamental aspect of innovation in materials science. In the ﬁeld of energy conversion, for example, the development of water-processed organic solar cells provides environmentally friendlier materials, which contribute to reduce health risks. Herein, a novel approach is described to produce water-soluble electron-donor single wall carbon nanotube (SWCNT) hybrids based on the noncovalent immobilization of quaternized pyridyloxy zinc phthalocyanines (ZnPc) with a varying number of pyridyl substituents. Moreover, the excellent electron-accepting ability of the latter ZnPcs is reported. The introduction of tert-butylphenyl groups at the pyridines enables for the ﬁrst time a complete characterization. The electron-acceptor nature of the ZnPcs enables switching the role of SWCNTs within the resulting supramolecular hybrids. Finally, a proof-of-concept demonstration of the SWCNT/ZnPc hybrids' capacity for energy conversion is presented, paving their way to possible use as active layer material in solar cells processed entirely from aqueous solutions.
EAM Import::2019-03-13

Rationalizing Fabrication and Design Toward Highly Efficient and Stable Blue Light-Emitting Electrochemical Cells Based on NHC Copper(I) Complexes - Weber, Michael; Fresta, Elisa; Elie, Margaux; Miehlich, Matthias; Renaud, Jean-Luc; Meyer, Karsten; Gaillard, Sylvain; Costa, Ruben Dario (Advanced Functional Materials, 2018)
Recently, the use of a new family of electroluminescent copper(I) complexes—i.e., the archetypal [Cu(IPr)(3-Medpa)][PF6] complex; IPr: 1,3-bis-(2,6-di-iso-propylphenyl)imidazole-2-ylidene; 3-Medpa: 2,2′-bis-(3-methylpyridyl)amine—has led to blue light-emitting electrochemical cells (LECs) featuring luminances of 20 cd m−2, stabilities of 4 mJ, and efficiencies of 0.17 cd A−1. Herein, this study rationalizes how to enhance these figures-of-merit optimizing both device fabrication and design. On one hand, a comprehensive spectroscopic and electrochemical study reveals the degradation of this novel emitter in common solvents used for LEC fabrication, as well as the impact on the photoluminescence features of thin-films. On the other hand, spectro-electrochemical and electrochemical impedance spectroscopy assays suggest that the device performance is strongly limited by the irreversible formation of oxidized species that mainly act as carrier trappers and luminance quenchers. Based on all of the aforementioned, device optimization was realized using ionic additives and a hole transporter either as a host–guest or as a multilayered architecture approach to decouple hole/electron injection. The latter significantly enhances the LEC performance, reaching luminances of 160 cd m−2, stabilities of 32.7 mJ, and efficiencies of 1.2 cd A−1. Overall, this work highlights the need of optimizing both device fabrication and design toward highly efficient and stable LECs based on cationic copper(I) complexes.
CRIS-Team Scopus Importer:2020-09-14
Keywords: blue electroluminescence; copper(I) complexes; light-emitting electrochemical cells; multi-layered device design; redox stability

Recent advances in multifunctional nanocarbons used in dye-sensitized solar cells - Costa Riquelme, Rubén Dario; Lodermeyer, Fabian; Casillas Pacheco, Ruben; Guldi, Dirk Michael (Energy and Environmental Science, 2014)
Throughout recent years the implementation of nanocarbons into dye-sensitized solar cells (DSSC) has resulted in important breakthroughs. The most relevant of them in this context are (i) the enhancement of charge transport and charge collection in nanocarbon-doped electrodes, (ii) the introduction of nanocarbon interlayers that simultaneously reduce the charge recombination and increase the charge collection efficiency, (iii) the use of nanocarbon-based, iodine-free, solid-state electrolytes featuring excellent diffusion coefficients and catalytic efficiencies, (iv) the use of novel nanocarbon-based hybrid dyes, and (v) the use of nanocarbons towards platinum-free counter electrodes. The first four aforementioned aspects are thoroughly described in this review. This journal is © the Partner Organisations 2014.

Review - Single-Walled Carbon Nanohorn-Based Dye-Sensitized Solar Cells - Lodermeyer, Fabian; Costa, Ruben Dario; Guldi, Dirk Michael (ECS Journal of Solid State Science and Technology, 2017)
Efforts in the broad field of dye-sensitized solar cells (DSSC) are governed by four key challenges: i) the development of photoelectrodes with high charge injection yields and charge collection efficiencies, ii) the development of low-cost buffer layers, which effectively reduce the back reaction of electrons from the transparent conductive oxide (TCO) to the electrolyte, iii) the design of platinum-free counter electrodes (CE), which feature good electrolyte regeneration yields, and iv) the implementation of (quasi) solid-state and iodine-free electrolytes featuring excellent ionic diffusion and conductivity. The introduction of nanocarbons into each component of DSSCs has emerged as a promising strategy to tackle all the aforementioned challenges. Leading examples of nanocarbons are graphene, carbon black (CB), multi-walled carbon nanotubes (MWCNT), and single-walled carbon nanotubes (SWCNT). Here, we focus on single-walled carbon nanohorns (SWCNH), which were successfully integrated into each of the aforementioned parts of DSSCs.
EAM Import::2019-03-13

Substituting TiCl4-Carbon Nanohorn Interfaces for Dye-Sensitized Solar Cells - Casillas Pacheco, Ruben; Lodermeyer, Fabian; Costa, Ruben Dario; Prato, Maurizio; Guldi, Dirk Michael (Advanced Energy Materials, 2013)
An easy-to-implement strategy to introduce carbon nanohorns as interlayers in the photoelectrode of a dye-sensitized solar cell without affecting its overall performance is presented. This provides a clean, easy, and ecofriendly alternative to achieve highly efficient cells.

Synergy of Catechol-Functionalized Zinc Oxide Nanorods and Porphyrins in Layer-by-Layer Assemblies - Burger, Alexandra; Kunzmann, Andreas; Costa, Ruben Dario; Srikantharajah, Rubitha; Peukert, Wolfgang; Guldi, Dirk Michael; Hirsch, Andreas (Chemistry - A European Journal, 2018)
Catechol-functionalized, positively charged ZnO nanorods (NRs) and anionic porphyrins were integrated into layer-by-layer (LbL) assemblies. In general, this study focuses on the impact that different porphyrins, varying in size and number of negative charges, exert on the LbL architecture in terms of morphology and spectroscopy. In particular, through a combination of analytical methods, including UV/Vis spectroscopy, SEM, and profilometry, valuable insights into LbL assembly formation were gathered. A key feature was the surface coverage in the resulting films. Denser films and surface coverages were realized when highly negatively charged and sterically demanding porphyrins were employed. As a complement to basic characterization, the LbL assembled films were used to fabricate proof-of-concept solar cells.
Keywords: porphyrins; solar energy conversion; layer-by-layer assemblies; layered compounds; thin films; ZnO nanorods

Tuning pentacene based dye-sensitized solar cells - Kunzmann, Andreas; Gruber, Marco; Casillas, Ruben; Tykwinski, Rik; Costa, Ruben Dario; Guldi, Dirk Michael (Nanoscale, 2018)

Tuning the stability of graphene layers by phthalocyanine-based oppv oligomers towards photo- and redoxactive materials - Brinkhaus, Linda; Katsukis, Georgios; Malig, Jenny; Costa, Ruben Dario; Garcia-Iglesias, Miguel; Vazquez, Purificacion; Torres, Tomas; Guldi, Dirk Michael (Small, 2013)
In contrast to pristine zinc phthalocyanine (1), zinc phthalocyanine based oPPV-oligomers (2-4) of different chain lengths interact tightly and reversibly with graphite, affording stable and finely dispersed suspensions of mono- to few-layer graphene - nanographene (NG) - that are photoactive. The p-type character of the oPPV backbones and the increasing length of the oPPV backbones facilitate the overall π-π interactions with the graphene layers. In NG/2, NG/3, and NG/4 hybrids, strong electronic coupling between the individual components gives rise to charge transfer from the photoexcited zinc phthalocyanines to NG to form hundreds of picoseconds lived charge transfer states. The resulting features, namely photo- and redoxactivity, serve as incentives to construct and to test novel solar cells. Solar cells made out of NG/4 feature stable and repeatable photocurrent generation during several 'on-off' cycles of illumination with monochromatic IPCE values of around 1%. Photoactive graphene hybrids: p-type oligo-para-phenylene vinylene zinc phthalocyanine oligomers exfoliate graphite, interact electronically with wet-chemically exfoliated graphite via charge transfer, and produce photocurrent upon illumination. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Using carbon nanodots as inexpensive and environmentally friendly sensitizers in mesoscopic solar cells - Margraf, Johannes; Lodermeyer, Fabian; Strauß, Volker; Haines, Philipp; Walter, Johannes; Peukert, Wolfgang; Costa, Ruben Dario; Clark, Timothy; Guldi, Dirk Michael (Nanoscale Horizons, 2016)
We discuss the use of carbon nanodots (CNDs) as sensitizers in mesoscopic solar cells. The CNDs are synthesized using a one-step, bottom-up microwave approach with citric acid, urea, and formic acid as precursors in aqueous media. Their light-harvesting capabilities can be tuned by adjusting the synthetic parameters. Comprehensive spectroscopic and theoretical studies allow us to rationalize the nature of their absorption features. Promising power conversion efficiencies ( extgreekh) of 0.24% can be achieved from these cheap and eco-friendly sensitizers by optimizing the solar-cell assembly process. Interestingly, we found that extending the light absorption towards longer wavelengths does not necessarily improve the performance of the solar cells, since the longer-wavelength absorption features hardly contribute to the cells' photo-action spectra, so that the overall power conversion efficiency is actually worse. The origin of the lower performance is corroborated in transient absorption spectroscopy and photovoltage decay measurements. Our work points, on one hand, to the limits of as-synthesized CNDs as photosensitizers and, on the other hand, to possible improvements.

White Light-Emitting Electrochemical Cells Based on Deep-Red Cu(I) Complexes - Fresta, Elisa; Weber, Michael; Fernandez-Cestau, Julio; Costa, Ruben Dario (Advanced Optical Materials, 2019)
The synthesis and characterization, as well as photoluminescent and electrochemical features of a series of ionic copper(I) complexes-, i.e., [Cu((NN)-N-<^>)((PP)-P-<^>)](+), where (NN)-N-<^> is 4,4 '-diethylester-2,2 '-biquinoline (dcbq) and (PP)-P-<^> is bis-triphenylphosphine, bis[2-(diphenylphosphino)phenyl)ether] (POP), or 4,5-bis(diphenylphosphino)-9,9-dimethylxanthene (Xantphos)-are reported along with their application to achieve both deep-red and white light-emitting electrochemical cells (LECs). In short, the first deep-red Cu(I)-based LECs featuring high irradiances (approximate to 100 mu W cm(-2)) and excellent color stability (x/y CIE color coordinates of 0.66/0.32) over days are reported. This is achieved by comparing the electroluminescent behavior of this series of complexes with respect to the irradiance and stability, as well as the impact of introducing supporting electrolytes on the device performance. This is rationalized using spectroscopic and electrochemical studies. Finally, the first white-emitting LEC is manufactured with red-emitting copper(I) complexes, achieving x/y CIE color coordinates of 0.31/0.32 and a high color rendering index of 92.
CRIS-Team WoS Importer:2019-10-04